Perbandingan Minat Belajar Antara Indoor Class dan Outing Class pada Siswa Sekolah Dasar - Subagja, Rizki; Ma'mun, Amung (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2024)
Learning interest is one of the important factors that affect the success of a student's learning; this is an essential concern that the teacher must consider. This study aimed to determine the learning interest of elementary school students in Indoor Class learning and outing class activity learning. The research method used is descriptive comparative. The population in this study was five public elementary schools in Bandung City. The sample numbered 364 students in grades 4, 5, and 6, consisting of 182 students who participated in outing class learning activities and 182 students who carried out indoor class learning. Researchers used a learning interest instrument with a reliability coefficient of 0.972 and a reliable interpretation value. Data analysis used is descriptive statistics and Independent Sample t Test test to analyze the comparison of 2 groups. The results showed that the percentage of indoor class learning was 46%, and learning in outing class activities was 54%. While analyzing the Independent Sample t-test results in Levene's Test for Equality of Variances data with a sig value. 0.000 is smaller than 0.05, so there are different variances. The Equality of Means data t-test results produce sig. (2-tailed) of 0.000 is smaller than 0.05, there is a difference, and outing class activities foster more student interest in learning. This finding is expected to be an evaluation material for related parties to build interest in learning and improve student learning outcomes.